PERANCANGAN MESIN PENCACAH PLASTIK BERPENGGERAK MESIN DIESEL 30 HP MENGGUNAKAN PERANGAT LUNAK AUTODESK INVENTOR 2017 - Wahyudin, Febri (Politeknik Harapan Bersama Tegal, 2023)
Abstract – Plastic is one type of waste whose volume is increasing, recycling plastic waste is the only way to reduce the amount of plastic waste. In this recycling process, the plastic is first chopped so that it is easy to recycle. One tool that can be used is a plastic chopping machine. This plastic chopping machine is supported by several components, namely the frame, diesel engine, axle shaft, pendulum, chopping knife, pillow block bearing, bottom funnel and filter, pulley, and V-belt. This study aims to design and analyze the stresses of the frame of the plastic chopping machine. The material used for the frame is ST37 carbon iron. The design and analysis was carried out using the Autodesk Inventor Professional software 2017. The simulation results show that the diesel engine mount has a mass, von Mises stress, deformation and safety factor of 82.327 kg, 22.01 MPa, 0.1846 mm, respectively. 4.21ul. And the simulation results on the axle holder have mass, von mises stress, deformation and safety factor of 82.327 kg, 0.7 MPa, 0.00936 mm, 15 ul.